1963
DOI: 10.6028/jres.067a.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two infrared bands of CH2D2

Abstract: T'Yo i~frared absorption bands of CHzDz have been analyzed in the semirigid rotor approXlmatlOn. These are the A-type band at 2671.67 em-I and the C-type band at 4425.61 em-I .. The A~type band has ~reviou sJy been assigned as Va+ V9, and the C-type band is tentatively assl~ned as va+ v6. rt:e ~pp er state of the A-type band is peTturbed presumably by the close I Ylll~ level 2V5 . rr:lus IllteractlOn has not been investigated . The following values were found for the rotatIOnal constants of the ground vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

1973
1973
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…Table summarizes the nine vibrational fundamentals as known today. A total of 22 vibrational bands had been studied at moderate to high resolution prior to the present work, where we reanalyze also three of the previously known bands. The far-infrared pure rotational spectrum has also been studied with the main goal of deriving the permanent dipole moment of CH 2 D 2 including the answer to the long standing question of its sign. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table summarizes the nine vibrational fundamentals as known today. A total of 22 vibrational bands had been studied at moderate to high resolution prior to the present work, where we reanalyze also three of the previously known bands. The far-infrared pure rotational spectrum has also been studied with the main goal of deriving the permanent dipole moment of CH 2 D 2 including the answer to the long standing question of its sign. , …”
Section: Introductionmentioning
confidence: 99%
“…A total of 22 vibrational bands had been studied at moderate to high resolution prior to the present work, where we reanalyze also three of the previously known bands. [48][49][50][51][52][53][54][55][56][57][58][59][60] The farinfrared pure rotational spectrum has also been studied with the main goal of deriving the permanent dipole moment of CH 2 D 2 including the answer to the long standing question of its sign. 61,62 In our two previous papers, we have complemented the lowenergy spectra by observing and analyzing previously undetected, weak, or forbidden transitions for example to levels of A 2 symmetry or weaker overtone and combinations levels.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution studies of the first overtone and combination bands have been reported in refs. [33][34][35][36] where the bands 5 , n 5 þ n 9 and 2n 3 were analyzed. It should be mentioned, however, that ro-vibrational transitions with J up to J max ¼ 9 were assigned for the bands included in refs.…”
Section: R E S E a R C H Pmentioning
confidence: 99%
“…C'est dans ce cadre qu'on obtient la numérotation des vibrations qui est utilisée ici. Le tableau I permet de faire la correspondance entre cette numérotation déjà employée par Olson [2] et la numérotation de la référence [6] qui rattache les vibrations de tous les dérivés isotopiques du méthane aux vibrations de la molécule CH4.…”
Section: Tableauunclassified
“…Dans la branche R nous avons mesuré une raie AALi = -2, AK, = + 3 à 1 277, 917 cm -1. Des raies résiduelles de la vapeur d'eau apparaissent à partir de 1 271 cm-1 mais ne sont vraiment gênantes qu'au-dessus de des résultats précédemment publiés par Olson et al [2] nous avons pu obtenir les valeurs des constantes rotationnelles du fondamental A°, B°, CI. Les informations en notre possession ne permettent pas de déterminer les 5 constantes de distorsion de Watson mais seulement 3 d'entre elles.…”
Section: Poids Statistiques De Spin Et Symétrie Desunclassified